Proceedings of the Seventh ACM Conference on Creativity and Cognition 2009
DOI: 10.1145/1640233.1640316
|View full text |Cite
|
Sign up to set email alerts
|

Predicting successful completion of online collaborative animation projects

Abstract: Online creative collaboration projects are started every day, but many fail to produce new artifacts of value. In this poster, we address the question of why some of these projects succeed and others fail. Our quantitative analysis of 892 online collaborative animation projects, or "collabs," indicates that the early presence of organizational and structural elements, particularly those of a technical nature, can predict successful completion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Specifically, unlike songs generated through recurring collaborations (see column (b)), for those generated through occasional collaborations (column (a)) applying technical tags is positively associated with the odds of being overdubbed at all. As regards prior work (see column (d)), our findings are somewhat in line with those reported by Luther et al [35] (see column (e)) who found that Newgrounds animations advertising technical specifications are associated with higher chances of reuse. Also, prior work on Wikipedia (e.g., [1,30,45,54]) has consistently found evidence that article metadata in Wikipedia are reliable proxies for article quality and, as such, they can be used as antecedents of page edits that will stick.…”
Section: Remix Factorssupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, unlike songs generated through recurring collaborations (see column (b)), for those generated through occasional collaborations (column (a)) applying technical tags is positively associated with the odds of being overdubbed at all. As regards prior work (see column (d)), our findings are somewhat in line with those reported by Luther et al [35] (see column (e)) who found that Newgrounds animations advertising technical specifications are associated with higher chances of reuse. Also, prior work on Wikipedia (e.g., [1,30,45,54]) has consistently found evidence that article metadata in Wikipedia are reliable proxies for article quality and, as such, they can be used as antecedents of page edits that will stick.…”
Section: Remix Factorssupporting
confidence: 93%
“…In [34] they found that the collaborations more likely to be completed are those initiated by experienced 'leaders' well-known to the community (as the number of views and likes received by animations helps build up their reputation), who are also inclined to communicate frequently. In another study on Newgrounds [35], they also found evidence that specifying technical constraints, such as the frame rate and background color of the animation, in collaboration descriptions is associated with a higher chance of their success. Settles and Dow [46] analyzed FAWM (February Album Writing Month), an online community for songwriters who collaborate every year to the creation of an entire album of songs in one month.…”
Section: Remix Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…In a second empirical study, I sought a deeper explanation of why some collabs succeed, yet most fail [7]. I quantitatively analyzed almost 900 collabs, using content analysis, logistic regression, and other statistical tests.…”
Section: Collabs Have Different Needs Than Wikipedia or Ossmentioning
confidence: 99%
“…Creative collaboration has drawn together diverse viewpoints [22] to support goals such as songwriting [5], animation [17] and remixing [10]. Storytelling, too, can be collaborative: if the author's role is to provide an authentic emotional experience for their story's audience [19], then the diverse perspectives and expertise of the crowd could support an author's search for the perfect character, setting, or plot.…”
Section: Introductionmentioning
confidence: 99%